On algebraic bases of algebras of block-symmetric polynomials on Banach spaces - V. V. Kravtsiv; A. V. Zagorodnyuk (Математичні Студії)
The paper contains a description of algebraic basis of algebra of block-symmetric polynomials on the l_1-sum of the copies of l_1.